Economic burden of dengue illness in India from 2013 to 2016: A systematic analysis. (July 2019) - Hariharan, Dhwani; Das, Manoja Kumar; Shepard, Donald S.; Arora, Narendra Kumar
Highlights: India had about 53 million symptomatic dengue in India in 2016. The overall cost of dengue in 2016 was about US5.71 billion with 14.3% due to fatal cases and 85.7% to non-fatal cases. The cost shares of non-fatal cases were; hospitalized-62.9%, ambulatory-17%, and non-medical cases-5, 8% of total costs. The aggregate cost estimate for 2016 is almost triple the original 2013 estimate. Abstract: Objectives: This paper concerns a systematic analysis of dengue illness and costs in India from 2013 to 2016. A previous study for 2006–2012 found that that projected annual number of dengue cases (5.78 million) was 282 times the officially reported number (20, 474), highlighting enormous uncertainty. Methods: This study updated primary data for India from 2012 to 2014 and synthesized the latest epidemiological and economic literature through 2018 using the country and global estimates. Results: The first empirically-based publication of dengue costs by country (in 2016) estimated India experienced 18, 618, 706 symptomatic dengue cases and 1602 deaths, and cost 1.51 billion in 2013. With a combination of increased incidence, more refined methods, and better data this 2018 study raised the latest estimates to 53, 210, 706 cases, 22, 527 deaths, and 5.71 billion economic costs for 2016, representing increases over the previous publication of 186%, 1306%, and 278%, respectively. When consistent methods and data were used to compare 2013 to 2016, the corresponding changes were only +29%, −9%, and +12%, respectively over these 3 years. Conclusions: India's burden of dengue is substantially greater than previously estimated. Although uncertainty intervals remain wide, these latest estimates reinforce the health and economic benefits that India would realize if dengue were substantially controlled.